2013
DOI: 10.1016/j.vetmic.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

PLGA nanoparticle entrapped killed porcine reproductive and respiratory syndrome virus vaccine helps in viral clearance in pigs

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a chronic viral disease of pigs, has been posing a huge economic concern to pig industry worldwide. In this study, we developed biodegradable PLGA [poly(d,l-lactide-co-glycolide)] nanoparticle-entrapped killed PRRSV vaccine (Nano-KAg), and administered intranasally to pigs once and evaluated the immune correlates. In Nano-KAg vaccinated homologous virus challenged pigs, complete clearance of viremia was observed in 2 weeks, associated with a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…It has been speculated that the efficacy of an inactivated vaccine is potentiallydetermined by the inactivation agent and/or the adjuvant [5254]. In this study, the BEI-inactivated vaccine successfully induced the SN antibody response and partially inhibited viremia.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been speculated that the efficacy of an inactivated vaccine is potentiallydetermined by the inactivation agent and/or the adjuvant [5254]. In this study, the BEI-inactivated vaccine successfully induced the SN antibody response and partially inhibited viremia.…”
Section: Discussionmentioning
confidence: 71%
“…BEI has successfully been used to inactivate PRRSV in previous studies [52,57,58]. In these previous studies, inactivated PRRSV vaccine induced effective immune responses after single intranasal administrations [53,54]. However, the intranasal vaccine delivery route requires an additional vaccine spray machine and has to be performed by well-trained staff.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypes and frequencies of lymphoid and myeloid cells populations from 50,000 events of immunostained LMNCs were determined by flow cytometry as described previously. 23 For intracellular IFN-γ staining, Monensin (GolgiPlug, BD Biosciences) was added during the last 6 hours of the 48-hour incubation of LMNCs that were unstimulated or stimulated with PRRSV MN184 KAg as described above. LMNCs were first immunostained using pig lymphocyte-specific monoclonal antibodies (CD3ε, CD4α, CD8α, CD56, and TcR1N4) conjugated with different fluorochromes.…”
Section: Flow-cytometric Analysesmentioning
confidence: 99%
“…19 Previously, we have shown that a single dose of PRRSV KAg-entrapped in PLGA (50:50) nanoparticle (NP-KAg) elicits both mucosal and systemic immune responses. 22,23 Recently, NP-KAg coadministered intranasally twice with M. tb WCL induced cross-protective anti-PRRSV immune response in blood to a challenged heterologous PRRSV, associated with a significant reduction in viremia. 14 In this report, we made use of various types of the lung samples of that recent study 14 to evaluate viral load and local mucosal immunity both at airway surfaces and in the lung parenchyma, and also microscopic lung histopathology in vaccinated, heterologous PRRSV-challenged pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation